Novel Fundus Camera Design - DeHoog, Edward Allen (The University of Arizona., 2008)
A fundus camera a complex optical system that makes use of the principle of reflex free indirect ophthalmoscopy to image the retina. Despite being in existence as early as 1900's, little has changed in the design of a fundus camera and there is minimal information about the design principles utilized. Parameters and specifications involved in the design of fundus camera are determined and their affect on system performance are discussed. Fundus cameras incorporating different design methods are modeled and a performance evaluation based on design parameters is used to determine the effectiveness of each design strategy. By determining the design principles involved in the fundus camera, new cameras can be designed to include specific imaging modalities such as optical coherence tomography, imaging spectroscopy and imaging polarimetry to gather additional information about properties and structure of the retina. Design principles utilized to incorporate such modalities into fundus camera systems are discussed. Design, implementation and testing of a snapshot polarimeter fundus camera are demonstrated.